2020
DOI: 10.3390/antibiotics9040172
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Melanogenesis by Fosfomycin in B16F10 Cells Through the Upregulation of P-JNK and P-p38 Signaling Pathways

Abstract: Fosfomycin disodium salt (FDS), which is a water-soluble extract, is a bactericidal drug used to inhibit the synthesis of cells. Moreover, it has been found to be effective in the treatment of urinary tract infections. The present study was conducted to investigate the melanogenesis-stimulating effect of FDS in B16F10 cells. Several experiments were performed on B16F10 cells: the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, the melanin content assay, the cellular tyrosinase activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…Consequently, individual 4 , 6 , 10 , and 12 did not increase melanin productions alone ( Figure S27 ) similar to those shown in Figure 4 , and it was suggested the abovementioned four compounds could merely enhance melanogenesis effects of α-MSH. Accordingly, additional signal pathways in melanogenesis, such as tyrosinase-related protein-1 (TRP-1), TRP-2, microphthalmia-associated transcription factor, melanocortin 1 receptor, cyclic adenosine monophosphate, protein kinase A, cAMP-response element-binding protein, c-Jun N-terminal kinases, extracellular signal-regulated kinase, p38, and phosphoinositide 3-kinase/protein kinase B [ 7 , 21 ], should be further tested and confirmed for those active components.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, individual 4 , 6 , 10 , and 12 did not increase melanin productions alone ( Figure S27 ) similar to those shown in Figure 4 , and it was suggested the abovementioned four compounds could merely enhance melanogenesis effects of α-MSH. Accordingly, additional signal pathways in melanogenesis, such as tyrosinase-related protein-1 (TRP-1), TRP-2, microphthalmia-associated transcription factor, melanocortin 1 receptor, cyclic adenosine monophosphate, protein kinase A, cAMP-response element-binding protein, c-Jun N-terminal kinases, extracellular signal-regulated kinase, p38, and phosphoinositide 3-kinase/protein kinase B [ 7 , 21 ], should be further tested and confirmed for those active components.…”
Section: Resultsmentioning
confidence: 99%
“…When exposed to the ultraviolet radiation of solar light or harmful chemicals and pathogenic factors, moderate melanogenesis can protect our skin from reactive oxygen species generation in keratinocytes and melanocytes [ 6 ]. Tyrosinase is an important enzyme in melanogenesis to produce more melanin for us to defense against aforementioned hazardous conditions [ 7 ]. Therefore, the active components of A. edulis are worthy to be clarified for further medical applications.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, our research team has studied the pathways involved in regulating pigmentation by treating melanocytes with specific substances or old antibiotics. It has also been suggested that these compounds or old antibiotics may be used as therapeutic or cosmetic agents [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we performed an experiment focusing on new efficacy of lincomycin. Recent studies have reported that several antibiotics isolated from Streptomyces species, such as tobramycin, fosfomycin (melanogenesis stimulator), and kanamycin (melanogenesis inhibitor), are related to melanogenesis [26][27][28]. However, the effect of lincomycin on melanogenesis has not yet been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Dct catalyzes the conversion of dopachrome into 5,6-dihydroxyindole-2-carboxylic acid (DHICA) which is subsequently changed to brown-black melanin (Eumelanin) by TRP-1 [ 7 ]. Thus, both up-regulated expression level and activated enzymatic function of tyrosinase family proteins dramatically increase melanin production in melanocytes [ 8 , 9 ]. As a key enzyme accelerating the first and rate-limiting step in melanin biosynthesis, the inhibition of tyrosinase is highlighted as a potential mode to treat hyperpigmentation.…”
Section: Introductionmentioning
confidence: 99%